(3QSGdI aj MOhK GdCLSGes - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg MeO GdTGcQjf dQH GdYGdejf gPG eG LeY ai GdOdGdGJ GdhGVMI hGdHQGgjf GdbGWYI Ydi MOhK GdGLSGe HGdOYGhi GdGQHY CeG GdcdGe ai GKHGJ GdGchGf ai GdLSe s
(3BNQgG (B:s
(3hGdHOjgI cd eG jYO ef ceGd GdYbd eeG jMUd dGYef WQjb GdJCdja eG UGQ Hg GdLhgQGf eJLGhQjf hGddg JYGdiCYde hQShdg Udi Gddg Ydjg hSde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B860s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd (B(703) s
Keywords: (3GdadSaI hGdefWbs